Implementation of Business Operational Strategy for Modern Nature Tourism Development "Le Hu Garden" - Mandalikha, Baiq Asry Afriza; Hamdi , Edi; Anindita , Rina; Munandar , Agus (Innovative: Journal Of Social Science Research, 2025)
Le Hu Garden Indonesia is a nature tourism service company established in 2016 in Deli Serdang, North Sumatra, which has a vision to become the top choice in leading tourist services by providing satisfactory service to customers totally. To achieve this vision, the right operational strategy using technology and sustainability or going green is needed. This research tries to see the application of development strategies for Le Hu Garden's business. The results showed that Le Hu Garden Operations is very important as the spearhead of the company's progress, this occurs due to the pattern of work that is service and related to technology so that all related aspects must be handled by the operational department. In addition, go green technology is the pulse of the company that is not easily imitated by competitors so that both park operations and supporting technology are priorities for the operational division. To ensure that the company continues to grow and maintain customer trust in the products offered, the company will continue to develop technology both in terms of investment and utilization of technology functions to continue to compete in the market and launch new supporting technologies to add value to products and increase the number of customers